ASSESSMENT OF BIOREMEDIATION POTENTIAL OF Spirogyra porticalis and Chlorella vulgaris ON COPPER AND CHROMIUM IN TANNERY EFFLUENT FROM CHALLAWA INDUSTRIAL AREA, KANO STATE (FUDMA JOURNAL OF SCIENCES, 2021)
Discharge of industrial effluent in aquatic environment is a serious threat to life due to toxic heavy metals. Algae can be used as cheap bioremediation agent in comparison to conventional technologies. This research was conducted to evaluate the bioremediation potential of two algal species i.e.Spirogyra spp. and Chlorella spp. for the removal of heavy metals from two tannery industries M Tannery and GB Tannery located in Challawa Industrial area by using Atomic Absorption Spectrophotometry (AAS Unicorn 969) and also Physicochemical parameters like pH, Temperature, EC, TDS, DO and BOD were measured. In GB Tannery, Spirogyra spp. had the highest affinity for Cr which was 50%, 67%, 50% at 3rd, 6th and 9th weeks interval respectively. Chlorella spp. showed highest affinity for Cu was 60% 85% and 93%. In M tannery, Chlorella spp. had the highest potential to remove heavy metals from the effluent, showing high affinity for Cu which was 80%, 92%, 59% at 3rd, 6th and 9th weeks respectively. Both algal species were not effective for Cr removal. Temperature ranged between 30-31˚C which might be as a result of ambient temperature, pH of both tanneries did not differ significantly and it was not within the maximum permissible limit of 6.5-8.5. EC of M Tannery was a little higher than GB Tannery (8.417±0.2627, 6.920±0.05000) which were below the permissible limit. TDS of M tannery is higher than that of GB Tannery 1919.0±68.462mg/l, 1916.0±61.944mg/l which were not within the permissible limit. DO content were within the permissible limits of
Keywords: Chlorella spp., Effluent, Physicochemical, Spirogyra spp., Tannery